THE CONTROLS ON THE COMPOSITION OF BIODEGRADED OILS IN THE DEEP SUBSURFACE-PART 1: BIODEGRADATION RATES IN PETROLEUM RESERVOIRS - Larter S.; Wilhelms A.; Head I.; Koopmans M.; Aplin A.; di Primio R.; Zwach C.; Erdmann M.; Telnaes N. (My University, 2003)
Biodegradation rates in oilfields have been assessed conservatively using whole oil-column minimum rate estimates, diffusion-controlled oil column compositional gradient modelling and mixed oil kinetic models. Biodegradation rate constants (first order) are around 10-6-10-7 yr-1 for hydrocarbons in the degradation zones these corresponding well with zero order field-wide minimum rate estimates of about 10-8 kg hydrocarbons/kg oil/year for the whole oil column. With biodegradation induction times of around 1-2 Ma to perturb an entire oil column for light oil reservoirs and 10-20 Ma for heavy oil reservoir degradation the results indicate that where we see continuous gradients in the oil columns, degradation must have been occurring episodically for many millions of years. To remove the n-alkanes from an oil (i.e. about 10% of an oil) around ca 15 Ma is needed for a heavy oil (ca 5 Ma for a light N. Sea oil). The timescales of oilfield degradation and filling are thus very similar and consequently the degree of biodegradation will be substantially controlled by oilfield charge history. Assessment of mixed degraded/non-degraded oil occurrence provides an independent confirmation that these rates are realistic and that timescales of degradation and field charging are similar. The maximum effective rate constant of degradation, ultimately controlled by the limiting effect of diffusion of alkanes to the oil water contact (OWC) (ca 10-4 yr-1 for a 130 m thick oil column first order rate constant) is well above the estimated rate constants indicating oil biodegradation rate is not limited by electron donor supply (i.e. hydrocarbons) but by supply of nutrients or oxidants. This suggests that diffusive transport of nutrients and electron acceptors in the aquifer to the site of biodegradation may be adequate to maintain the low rate biosphere.